THE MEDIATING ROLE OF STRATEGIC RENEWAL IN THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND IMPROVING FINANCIAL PERFORMANCE - Roqaya Kazem Al-Murshidi; Maydia Hassan Madhi; Dr. Saadia Haief Kadhum (Scholar Express Journals, 2023)
Many variables have appeared in the work environment and have a direct impact on the organization ’s activity. As a result of technological developments and the intensification of competition, the need has emerged to address these obstacles, find quick solutions and address their effects on the organization’s environment. The current research deals with important and necessary variables in the activity of the organization. Transformational leadership as an independent variable and its dimensions are represented by (ideal influence, intellectual stimulation, individual considerations, and empowerment) and the Mediating variable is strategic renewal. As for its dimensions, they are (exploration, entrepreneurship, investment opportunities, leadership participation). The dependent is the financial performance. Strategic renewal plays a partial “mediating role in the relationship between (transformational leadership and financial performance)”. It is concluded through the relationship between the three variables that is the independent variable (transformational leadership) whose influence is maximized on the dependent variable (financial performance) through the interaction of the intermediate variable exploratory strategic renewal at the macro level. And there is a direct significant effect of the independent variable (transformational leadership) on the dependent variable (financial performance). Therefore, the researchers recommend supporting new and innovative ideas at work, urging individuals to participate in decision-making and expressing their views at work
Keywords: strategic renewal; financial performance; transformational leadership